Utilization Menu Based on Food Local with Literacy Digital Against Handling Stunting - Juana Linda Simbolon; Emilia Silvana Sitompul (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Stunting is a condition of growth failure in toddlers that has lifelong impacts on their health, human resources, and economic growth. The results of the Indonesian Nutrition Status Survey (SSGI) show that the prevalence of stunting in Indonesia decreased from 24.4% in 2021 to 21.6% in 2022 . The target prevalence of stunting in Indonesia is 14% by 2024. The incidence of stunting in North Tapanuli is already chronic, with the prevalence of stunting increasing from 26.7% in 2021 to 27.4% in 2022. The selection of animal protein from local food sources with digital literacy is expected to accelerate the reduction of stunting. This study aims to analyze the effect of using a local food-based menu and applying digital literacy to increase the height of stunted children. This type of research is a quasi-experimental study using pre- and post-tests with a control group design in July-September in North Tapanuli Regency to compare the increase in height gain with local food. The sample consisted of 34 stunted children aged 12-60 months. Height measurements were taken every month after three months of intervention. Data were analyzed using a T-test with a 95% confidence level. This study showed that local food-based menus with digital literacy could increase the height of children aged 12-60 months p-value: was 0.014 <0.05. In the control group (without receiving local food-based menu intervention with digital literacy), there was no effect on increasing height p-value 0.125>0.05. The application of a local food-based menu with the use of digital literacy has an effect in increasing the height of children who are stunted, digital literacy can help parents access information, and educate families, through applications and social media so that this research is important, useful to introduce a new approach in handling stunting, namely combining local food with digital literacy. Keyword: Utilization of Local Food, Digital Literacy, Handling Stunting